Development of control unit for parameters of material processing modes - A. P. Morgunov; V. V. Derkach; I. V. Kirgizova (Омский научный вестник)
The use of modern energy and resource-saving technologies in multifactor technological processes is a promising direction for development of the manufacturing sector in most developed countries. The purpose of the work is to develop a control system for the Arduino UNO program with the parameters of material processing mode. The article describes the results of the development and creation of a control system for the parameters of the material processing mode in an electrochemical installation. As a result of the experiments, a control unit system was developed with automatic programming with predetermined cycles focused on changes in the macro deviations of the shape of the processing blank.